On Intracultural Idiolectal Phrasemes Coined by a Politician from a Translational Perspective. A Case Study: Problem Areas in Translating Jarosław Kaczyński’s phraseology (PHRASIS | Rivista di studi fraseologici e paremiologici, 2019)
The aim of the paper is to discuss intracultural idiolectal phrasemes coined by a politician from a translational perspective with a view to determining and highlighting potential problem areas. Their idiolectal nature and underrepresentation in bilingual lexicographic works pose linguo- cultural difficulties in the process of translation. In order to analyze the phenomenon of transferring a politician’s idiolectal phraseology into another linguo-cultural reality, a case study will be offered: this aspect will be discussed on the example of the problem areas in translating Polish phrasemes coined or popularized by Jarosław Kaczyński into English. The study will analyse chosen issues in order to emphasize the most important difficulties in the process of translation.
Keywords: idiolect, phraseme, political discourse, translation